The Brave New World of Lawyers in Japan: Proceedings of a Panel Discussion on the Growth of Corporate Law Firms and the Role of Lawyers in Japan - Aronson, Bruce E. (Columbia Journal of Asian Law, 2007)
A long-standing image of Japan is one of a closed, informal society which functions without resort to the legal system and lawyers. This image likely results from two sets of factors. First, popular views of Japan have long emphasized the importance of cultural values and the unimportance, if not active dislike, of law and lawyers in Japanese society. Initial efforts by both Japanese commentators and Western generalists in comparative legal studies focused on cultural explanations, such as a supposed lack of “legal consciousness” in Japan, in order to explain Japan’s early economic advances despite a relative lack of litigation or other use of formal law.’ This supposed lack of law was transformed into a virtue in the 1980s, as Americans decried a “litigation explosion” in the United States and looked enviously at a Japanese system which was perceived to elevate engineers over lawyers.2 Japanese law specialists criticized this presumed cultural preference for informality over law as oversimplified and exaggerated.3 They provided a number of alternative explanations for Japan’s litigation rate and the role of its legal system, such as institutional factors,4 economic analysis,5 and informal bureaucratic controls,6 all of which gave a greater role to formal law. However, this research had little impact on our popular image of Japan.